Sustainable Coral Reef Ecosystem Management in Palopo City Territorial Waters - Muhammad Bibin (Magister Ilmu Administrasi Publik, 2020)
Damage to coral reefs in the waters of Palopo City poses danger to the productivity of the habitat. Therefore, carrying out the adopting the principles of a conservation in the use and management of coral reefs in Palopo City area waters through an integrated system and participation of multi-stakeholders is considered imperative. The study analyzed the level and causes of damage coral reefs, assessed the role of stakeholders in managing coral reef ecosystems, and formulated a strategic model for managing coral reef ecosystems in Palopo City waters. Methods of data analysis included assessment of coral reef condition, stakeholder analysis, and hierarchical analysis. Result showed that fishing activity using environmentally unfriendly gear such as fish bombs and potassium is one of the principal causes of damage to coral reefs in the waters of Palopo City. Most damage occured to coral reefs at a depth of 4 meters at station 1, which registered a the percentage of the mortality index of 82.07%. Meanwhile, the least damage was 69.73%. At the depth of 4 meters station two is Result of stakeholder mapping identified three groups inter alia, contest setters, key players, and subject. The first priority strategy in the management of coral reef ecosystems in the waters of Palopo City should be designate the zoning of coastal areas, coordination among stakeholders that are relevant and important with respect to coral reef ecosystems power relations, drafting local regulations that mandate sustainable use and management of coral reef ecosystems and increasing training programs for fishing communities.